2016
DOI: 10.1002/hyp.10883
|View full text |Cite
|
Sign up to set email alerts
|

Active layer hydrology in an arctic tundra ecosystem: quantifying water sources and cycling using water stable isotopes

Abstract: Climate change and thawing permafrost in the arctic will significantly alter landscape hydro-geomorphology and the distribution of soil moisture, which will have cascading effects on climate feedbacks (CO2 and CH4), and plant and microbial communities. Fundamental processes critical to predicting active layer hydrology are not well understood. This study applied water stable isotope techniques ( 2 H and  18 O) to infer sources and mixing of active layer waters in a polygonal tundra landscape in Barrow, Alask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 66 publications
0
59
0
Order By: Relevance
“…Of the 62 mm of precipitation that was recorded between 10/10/2012 and 6/11/2013 at the Utqiaġvik weather station, 20% fell during the 2013 Pre-Melt and Melt Periods.The available isotopic data from those precipitation events suggest all were near the LWML(Throckmorton et al, 2016). The somewhat lower value estimated for the 2013 Winter Period at the BEO is likely a consequence of the cold temperatures and mild wind speeds, which reduce snow sublimation through reduced available energy for phase transfer and reduced blowing snow fetch distances, respectively.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Of the 62 mm of precipitation that was recorded between 10/10/2012 and 6/11/2013 at the Utqiaġvik weather station, 20% fell during the 2013 Pre-Melt and Melt Periods.The available isotopic data from those precipitation events suggest all were near the LWML(Throckmorton et al, 2016). The somewhat lower value estimated for the 2013 Winter Period at the BEO is likely a consequence of the cold temperatures and mild wind speeds, which reduce snow sublimation through reduced available energy for phase transfer and reduced blowing snow fetch distances, respectively.…”
mentioning
confidence: 91%
“…an average of +2.7‰Áday −1 , and δ 18 O increased an average of +0.53‰Áday −1 . The isotopic composition of wedge ice or textural ice can be highly variable however(Throckmorton et al, 2016), and greater efforts isotopically characterize Arctic water source terms should be made to confirm this preliminary observation. The fraction of surface water lost to evaporation during the Post-Melt Period was estimated using the method described in Section 2.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The stable isotopes of water ( 2 H and 18 O) are the most common components of natural water (Aragúas‐Aragúas, Froehlich, & Rozanski, ; Dansgaard, ). The relative abundance of stable water isotopes is an important signature for distinguishing water bodies and for characterizing the hydrological cycle (Grafenstein, Erlenkeuserb, Müllera, Trimborn, & Alefs, ; Throckmorton et al, ; Zhang, Guan, Zhang, Zhang, & Yao, ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to limited 25 drainage in the flat coastal plain, the frozen cores analyzed here are representative of field conditions for much of the thaw season. Water isotope analysis demonstrated that most water in the deep active layer comes from summer precipitation rather than seasonal ice melt (Throckmorton et al, 2016). Precipitation during September and October 2011 was above average for Barrow (http://climate.gi.alaska.edu/), suggesting a high water table during the winter freeze-up before we collected soil cores in early 2012.…”
mentioning
confidence: 98%